Using the Assemblr Application in English learning - Hilman; Nabila Putri, Nurhalyza; Yulia Sangkarini, Dhiza; Asyifah Madaniyah, Nurul (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2024)
This research was conducted to test reading comprehension of English text using the Assemblr edu application to 6th-grade elementary students in SD IT Widya Cendekia. In data processing techniques, researchers used descriptive method with several research instruments that use the Scale Guttman questionnaire to collect and analyze data, descriptive statistics, and the use of Interview data collected and analyzed through qualitative methods with a descriptive approach. To make learning more relevant to students lives and to increase their motivation in reading we provide technology as one of the learning media to be used. For this reason, Augmented Reality-Based Learning is the choice of researchers to be implemented in this learning practice. The Assemblr edu program is one of the augmented reality tools accessible for educational purposes. Furthermore, the Assemblr edu application has some special capabilities of its own for Augmented Reality projects. For example, using 2D and 3D graphics, music, and video is simple even for those without any programming experience. It has several viewpoints, is editable, and accessible from any location. The research study of augmented reality application development reality states that applications based on augmented reality are actually legal and have a practical point of view. Furthermore, the application's instructions are easy to follow.